Applications of Liquid Chromatography-Isotope Ratio Mass Spectrometry in Geochemistry and Archaeological Science - Blyth, Alison; Smith, C. (The Royal Society of Chemistry, 2014)
Liquid chromatography–isotope ratio mass spectrometry (LC-IRMS) is a relatively recent analytical development in the field of compound-specific isotope analysis. Its main advantage lies in allowing the analysis of compounds which are either not amenable to GC-IRMS, or which require derivatisation to be resolved on a gas chromatography column. A second advantage of an LC-IRMS system is the ability to use a flow injection mode to analyse bulk samples. A limitation of the technique is the restriction of analysis to compounds that are soluble in inorganic aqueous phases. Since the first commercial units became available in 2004, the technique has been applied in diverse fields including nutritional and biomedical research, food authentication, archaeology, and geo- and environmental sciences. Compound-specific analyses are available for amino acids, for example analysing bone and tooth collagen in archaeological science; volatile fatty acids used when investigating biogeochemical processes, particularly in extreme environments; plant carbohydrates, important to the study of carbon cycling as they are central to many food webs as substrates; and amino sugars, significant because microbial communities in soil play a vital role in carbon cycling and sequestration. Bulk isotope analyses can be conducted on water and δ13C of organic matter preserved in speleothems.